2018
DOI: 10.1007/s00592-018-1265-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of bone morphogenetic protein 6 (BMP6) in glucose homeostasis

Abstract: Aims Bone morphogenetic proteins (BMPs) are involved in the development and homeostasis of multiple organs and tissues. There has been a significant focus on understanding the role of BMPs in pancreatic β-cell dysfunction associated with type 2 diabetes (T2D). Our objective was to investigate the relationship between BMP6 and glucose homeostasis. Methods Ob / ob mice were treated with BMP6 for 6 days and analyzed for insulin rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Heterozygous deletion of the type 1 BMP receptor, Bmpr1a causes impaired glucose tolerance [49], while adipocyte-specific receptor deletion does not [50]. Similar salutary effects of glucose homeostasis have been observed in mice treated with BMP6, BMP7, and BMP9 [28,30,31]. BMPs can drive cellular differentiation including potentiation of brown and beige fat activation [47,48,51].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Heterozygous deletion of the type 1 BMP receptor, Bmpr1a causes impaired glucose tolerance [49], while adipocyte-specific receptor deletion does not [50]. Similar salutary effects of glucose homeostasis have been observed in mice treated with BMP6, BMP7, and BMP9 [28,30,31]. BMPs can drive cellular differentiation including potentiation of brown and beige fat activation [47,48,51].…”
Section: Discussionmentioning
confidence: 82%
“…Members of the TGF- superfamily, including BMPs, GDFs, and TGF- proteins can affect insulin sensitivity, cellular differentiation, and obesity [28][29][30][31]. These proteins typically work either through BMP-type receptors or TGF-−type receptors.…”
Section: Gdf3 Limits Bmp Signalingmentioning
confidence: 99%
“…In our study, we did not observe gross appearance of HO at the peritoneal injection site with the dose we selected. Moreover, given that previous studies investigating systemic treatment with doses of BMP6 ranging from 1 to 50 ng per gram of mouse weight reported no HO was found , the dose of 10 ng per gram of animal weight seems to be safe and we think there is still room for increasing the dose of injection before safety is compromised. The frequency of injection is another critical variable that should be considered for safety and effectiveness of BMP6 injection.…”
Section: Discussionmentioning
confidence: 92%
“…BMPs have recently been implicated in pancreas development, control of adult glucose homeostasis, energy expenditure by stimulation of brown adipose tissue formation [ 37 ], and the development of diabetic complications [ 38 ]. In particular, BMP-9 [ 39 ] and BMP-6 [ 40 ] improve glycemia and insulin resistance in T2DM mice and regulate glucose metabolism in hepatocytes. An in vivo human study confirmed that circulating BMP-9 levels are significantly higher in healthy subjects than in patients with newly diagnosed T2DM, and found a negative correlation with metabolic control, as assessed by HbA1c and fasting blood glucose [ 41 ].…”
Section: How Bone Active Therapies Affect Glucose Metabolismmentioning
confidence: 99%